Representações Sociais de Famílias para Profissionais do SUAS - ANA MARIA DE OLIVEIRA ESPINDOLA (2025)
The National Social Assistance Policy (PNAS) has objectives in its scope that aim to assist those who are in conditions of social vulnerability, through its functions of inclusion, prevention, promotion and protection. To this end, it establishes in the Unified Social Assistance System (SUAS) the axis of socio-family matrix as one of its fundamental principles, highlighting the relevance of the family as an essential basis for the effectiveness of programs, projects and services. In social assistance, a relationship of interdependence is established between the legal and institutional devices and the practices developed by professionals who execute this policy. The duties of psychologists and social workers in the SUAS are supported by a theoretical, operational and legal framework, but are also based on discourses and decisions that reflect the adoption of their values. In this sense, the research question emerges, which asks: What are the social representations about family for psychologists and social workers in the SUAS? The research aimed to analyze the social representations of social workers and psychologists from the Social Assistance Reference Centers (CRAS) in Mato Grosso do Sul, MS, about family. For this purpose, the Theory of Social Representations (TRS), formulated by Moscovici and collaborators, was used as a theoretical basis, taking as reference the dynamic nature of social representations and their function in guiding social practices. The study also conducted dialogue with authors who discuss public social assistance policies. It is characterized as a qualitative research, which uses semi-structured, organized and categorized interviews as a data collection instrument. Using the content analysis proposed by Bardin, the analysis was based on the theoretical frameworks of TRS and other authors. The results revealed a tension between the maintenance of hegemonic representations and the attempt to inclusively resignify these conceptions. On the one hand, professionals recognize the plurality of family arrangements and the need to deconstruct normative models. On the other hand, stigmas and prejudices persist, categorizing families served as deviations from an idealized standard. Professionals also attribute different meanings to families, combining recognition of diversity and reinforcement of stereotypes. Aspects such as personal and religious values were identified as significant influences, constituting practices and representations about families. Emancipatory representations, which value autonomy and the plurality of family configurations, contrast with conservative and family-oriented views that are still prevalent. The research showed that social assistance operates in a context of structural inequalities and that professionals face challenges in balancing family demands and institutional limitations. Despite the difficulties, there are increasing efforts to adopt more inclusive and collaborative practices, promoting rights and social justice. It is concluded that the Theory of Social Representations was an effective analytical tool, offering an in-depth understanding of professional practices and the challenges faced in the context of social assistance. However, the study highlights the need for future research to consolidate more inclusive and theoretically based practices in the social assistance field. Keywords: Social Representations; Social Assistance; Unified Social Assistance System/SUAS; Family.